STRATEGI PEMBERDAYAAN PENGENTASAN KEMISKINAN PADA PNPM MANDIRI - Sukidjo, Sukidjo (Jurnal Cakrawala Pendidikan, 2010)
Abstract Poverty eradication is one indicator of the success of the development attempts. Poverty is a complex and multidimensional problem. Attempts to eradicate poverty that have been made so far are not successful because they focus only on economic aspects, not on empowerment and involvement of the local people by establishing local societal institutions. Autonomous PNPM is a program to eradicate poverty that is based on empowerment through learning by (1) creating an atmosphere accommodating values of universal humanitarianism, societal principles and sustainable development (2) strengthening local societal institutions, (3) strengthening potentials through funding, training, and environmental development, and (4) protecting the certainty of the programs for the poor. Keywords: poverty, empowerment, autonomous PNPM